Overview of the Initial Implementation of the Nutritious Meal Program (MBG) and the Readiness of Health Infrastructure at SDN 52 Kendari - Devi Savitri Effendy; Afifah Azhari Dzulzahabiyyah; Inayah Fadhillah Silondae; Syarah Wahyuni Iriadi; Rahmat Bahnan; Amelia Putri (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: The Free Nutritious Meal Program (MBG) is one of the Indonesian government’s initiatives to improve students’ nutritional status and overall health in elementary schools. The program aims to address malnutrition issues, enhance students’ concentration during learning, and foster healthy eating habits from an early age. However, the success of MBG implementation does not rely solely on the provision of nutritious food but also on the readiness of school health infrastructure, including the availability of clean water, a functional school health unit (UKS) room, hygienic eating facilities, and proper waste management systems. Objective: This study aims to provide a comprehensive overview of the early implementation of the MBG program and assess the readiness of school health infrastructure at SDN 52 Kendari. Methods: This research employed a quantitative descriptive method using a survey approach with a closed-ended questionnaire. Respondents included teachers, parents, and students, totaling 154 participants. Data were analyzed descriptively using SPSS software to obtain frequency and percentage distributions for each indicator. Results: The results showed that the initial implementation of the MBG program at SDN 52 Kendari has been running effectively (78%), particularly in terms of regular food distribution, cleanliness during food preparation, and school involvement in monitoring food quality. Nevertheless, several infrastructure aspects still require improvement, such as handwashing facilities, toilet cleanliness, and food waste management. Conclusion: Overall, the implementation of the MBG program has had a positive impact on improving students’ learning motivation and strengthening cooperation between schools, parents, and the surrounding community. These findings indicate that the success of the MBG program cannot be separated from adequate supporting infrastructure. Therefore, continuous collaboration among local governments, schools, and communities is essential to strengthen health facilities and ensure the sustainability of the MBG program in the future. Keywords: Free Nutritious Meal Program, School Health Infrastructure, Nutritional Status, Program Implementation.